Amygdala growth from youth to adulthood in the macaque monkey. Issue 18 (19th June 2019) - Schumann, Cynthia M.; Scott, Julia A.; Lee, Aaron; Bauman, Melissa D.; Amaral, David G.
Abstract: Emerging evidence suggests that the human amygdala undergoes extensive growth through adolescence, coinciding with the acquisition of complex socioemotional learning. Our objective was to longitudinally map volumetric growth of the nonhuman primate amygdala in a controlled, naturalistic social environment from birth to adulthood. Magnetic resonance images were collected at five time‐points in 24 male and female rhesus macaques from 6 months to adulthood at 5 years. We then compared amygdala growth to other brain regions, including newly collected isocortical gray and white matter volumes, and previously published data on the same cohort. We found that amygdala volume increases by nearly 50% from age 6 months to 5 years. This dramatic growth is in contrast to overall brain and hippocampal volume, which peak near 3 years, white matter, which slows from 3 to 5 years, and isocortical gray, which has a net decrease. Similar to isocortical gray and hippocampal volumes, amygdala volume is ~8% larger in males than females. Rate of growth does not differ by sex. Although the underlying neurobiological substrate for protracted amygdala growth into adulthood is unclear, we propose it may be due in part to the unique cellular development of immature neurons in paralaminar nucleus that mature in size and connectivity with age. Prolonged amygdala maturation raises the possibility that environmental and genetic perturbations that disrupt this trajectory may contribute to the emergence of psychiatric disorders, such as anxiety, depression, schizophrenia, and autism; all in which the amygdala is strongly implicated. Abstract : Amygdala, isocortical gray, and cerebral white matter volumes were measured longitudinally in 24 male and female rhesus macaques reared in a controlled, naturalistic social environment. Amygdala volume increases by nearly 50% from 6 months to 5 years. This dramatic growth is in contrast to overall brain and hippocampal volume, which peak near 3 years, white matter, which slows from 3 to 5 years, and isocortical gray, which has a net decrease. Prolonged amygdala maturation raises the possibility that environmental and genetic perturbations that disrupt this trajectory may contribute to the emergence of psychiatric disorders, such as anxiety, depression, schizophrenia, and autism; all in which the amygdala is strongly implicated.